Preparation method of red phosphorus modified lithium-rich manganese-based positive electrode material, positive electrode plate and lithium ion battery

By modifying the lithium-rich manganese-based positive electrode material by red phosphorus, the problem of low stability and efficiency of the material in high specific energy battery applications is solved, and the high capacity and long cycle performance are improved, and the discharge specific capacity and cycle retention rate are significantly improved.

CN119133389AActive Publication Date: 2024-12-13UNIV OF SCI & TECH OF CHINA

Patent Information

Application Number
CN202411215018.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have low efficiency, severe voltage attenuation and multiplier ratios in high-specific energy battery applications due to lattice oxygen loss, interface side reaction, poor ion conductivity and spinel phase transition. Poor performance and cycle stability, making it difficult to meet the needs of high capacity and long cycles.

Method used

Using the red phosphorus modification method, lithium-rich manganese-based positive electrode material and red phosphorus are calcined in a vacuum state to form a phosphate coating and spinel, achieving element doping and coating, and improving the structural stability and electrochemistry of the material. performance.

Benefits of technology

Effectively improve the cyclic stability and first-time Coulomb efficiency of lithium-rich manganese-based cathode materials. The discharge specific capacity reaches 250-300mAh/g at 0.1C current density, and the retention rate is 75%-95% at 1C current density, which significantly improves the Reversible specific capacity and long cycle performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005021806480000011
    Figure HDA0005021806480000011
  • Figure HDA0005021806480000012
    Figure HDA0005021806480000012
  • Figure HDA0005021806480000021
    Figure HDA0005021806480000021
Patent Text Reader

Abstract

The invention provides a preparation method of a red phosphorus modified lithium-rich manganese-based positive electrode material, a positive plate and a lithium ion battery, and the preparation method comprises the following steps: mixing the lithium-rich manganese-based positive electrode material and red phosphorus in a mass ratio of 1: 0.001-0.01, and calcining for 1-6 hours at 300-600 DEG C in a vacuum state to obtain the red phosphorus modified lithium-rich manganese-based positive electrode material, the chemical general formula of the lithium-rich manganese-based positive electrode material is Li < 1 + x > Mn < 1-x > Ni < 1-x > 2Co < 1-x > 3O < 2 >. The method is low in raw material price and simple in reaction process. After red phosphorus is heated and sublimated at a high temperature, the red phosphorus and the lithium-rich manganese-based positive electrode material are subjected to a gas-solid interface reaction, a phosphate coating is generated on the surface of the positive electrode, spinel and oxygen vacancies are formed at the same time, P doping is realized in the positive electrode, and the reversibility and the structural stability of anion oxidation reduction of the lithium-rich manganese-based positive electrode material are effectively improved; the first coulombic efficiency, the reversible specific capacity and the long cycle stability of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of positive electrode materials, and in particular relates to a preparation method of a red phosphorus-modified lithium-rich manganese-based positive electrode material, a positive electrode sheet and a lithium ion battery. Background Art

[0002] Electrochemical energy storage plays an indispensable role in energy storage systems. Battery materials determine the overall performance of batteries and energy storage modules. Advanced battery materials need to meet the five requirements of high power density, high energy density, low cost, long life and environmental protection. At present, traditional cathodes have low specific capacity (<200mAh g -1 ) cannot fully meet the rapid development of high-energy-density batteries. Among the layered oxide positive electrode materials derived from LiCoO2, the lithium-rich manganese-based positive electrode has a higher practical specific capacity and energy density. In order to meet the growing energy demand for long driving mileage, the development of more than 500Whkg -1 High-capacity cathode materials are very necessary.

[0003] Lithium-rich manganese-based cathodes stand out due to their extremely high specific capacity and energy density, as well as their high voltage and low cost advantages, and are the next generation cathode materials with the greatest application potential. However, it is currently difficult to commercialize them due to reasons such as severe lattice oxygen loss, severe interfacial side reactions, poor ionic conductivity, and spinel phase transition during long cycles. As a result, these problems lead to low first coulombic efficiency, severe voltage decay, and poor rate performance and cycle stability. Among them, voltage decay increases the difficulty of battery management systems in practical applications.

[0004] In order to solve these problems, researchers have proposed a series of solutions for lithium-rich manganese-based cathode materials, including element doping, coating and surface treatment, and optimization of synthesis methods. However, using a single solution can only solve one of the above problems and it is difficult to achieve better results. Therefore, developing a solution that can simultaneously perform element doping and coating is of great significance for improving the cycle stability and electrochemical performance of lithium-rich cathode materials. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a preparation method of a red phosphorus modified lithium-rich manganese-based positive electrode material, a positive electrode sheet and a lithium-ion battery. The preparation method realizes dual modification of element doping and coating, and the process is simple; the cycle stability and first coulombic efficiency of the lithium-rich manganese-based positive electrode material treated with red phosphorus at high temperature are effectively improved.

[0006] The present invention provides a method for preparing a red phosphorus-modified lithium-rich manganese-based positive electrode material, comprising the following steps:

[0007] The lithium-rich manganese-based positive electrode material and red phosphorus are mixed in a mass ratio of 1:0.001-0.01, and calcined at 300-600° C. for 1-6 hours under a vacuum state to obtain a red phosphorus-modified lithium-rich manganese-based positive electrode material;

[0008] The general chemical formula of the lithium-rich manganese-based positive electrode material is: Li 1+x Mn 1-x1 Ni 1-x2 Co 1-x3 O2, x=0.01~0.3, 2+x=x1+x2+x3, x1=0.3~0.6, x2=0.7~1, x3=0.8~1.

[0009] Preferably, the particle size of the red phosphorus is 10 to 200 μm;

[0010] Red phosphorus is in gaseous state.

[0011] Preferably, the vacuum degree in the vacuum state is 0.01 MPa to 0.2 MPa.

[0012] Preferably, the temperature is increased to 300-600° C. at a heating rate of 2-8° C. / min.

[0013] Preferably, the lithium-rich manganese-based positive electrode material is: Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

[0014] Preferably, the lithium-rich manganese-based positive electrode material is prepared according to the following method:

[0015] Nickel salt, manganese salt, cobalt salt and lithium salt are dissolved in a mixed solution of acrylic acid and deionized water, and an aqueous solution of ammonium persulfate is added. After stirring for 55 to 65 minutes, the temperature is raised to 80°C and kept warm for 170 to 190 minutes for reaction, and then the temperature is raised to 120°C and kept warm for 11 to 13 hours for drying, grinding and two-stage calcination: the first stage calcination temperature is 300 to 600°C and the time is 3 to 7 hours; the second stage calcination temperature is 750 to 950°C and the time is 9 to 15 hours.

[0016] The present invention provides a positive electrode sheet, which is prepared by coating a positive electrode slurry on a positive electrode current collector;

[0017] The positive electrode slurry includes a red phosphorus-modified lithium-rich manganese-based positive electrode material prepared by the preparation method of the above technical solution.

[0018] The present invention provides a lithium ion battery, comprising a negative electrode sheet, an electrolyte, a separator and the positive electrode sheet described in the above technical solution.

[0019] Preferably, the separator is a PP separator; the negative electrode sheet is a metal lithium sheet;

[0020] The lithium salt in the electrolyte is LiPF6, and the solvent is a mixed solvent of EC / DEC with a volume ratio of 1:1.

[0021] The invention provides a method for preparing a lithium-rich manganese-based positive electrode material modified by red phosphorus, comprising the following steps: mixing the lithium-rich manganese-based positive electrode material and red phosphorus at a mass ratio of 1:0.001-0.01, calcining at 300-600°C for 1-6h under a vacuum state to obtain the lithium-rich manganese-based positive electrode material modified by red phosphorus; the chemical general formula of the lithium-rich manganese-based positive electrode material is: Li 1+ x Mn 1-x1 Ni 1-x2 Co 1-x3 O2, x = 0.01 ~ 0.3, 2 + x = x1 + x2 + x3, x1 = 0.3 ~ 0.6, x2 = 0.7 ~ 1, x3 = 0.8 ~ 1. This method has low raw material price and simple reaction process. After red phosphorus is sublimated by high temperature heating, it reacts with lithium-rich manganese-based positive electrode materials at the gas-solid interface to produce a phosphate coating on the surface of the positive electrode, and at the same time forms spinel and oxygen vacancies, realizing P doping inside the positive electrode, effectively improving the reversibility and structural stability of the anion redox of the lithium-rich manganese-based positive electrode materials, and improving the first coulomb efficiency, reversible specific capacity and long cycle stability of the materials. The experimental results show that the discharge specific capacity of the lithium-rich manganese-based positive electrode material of the present invention is 250 ~ 300mAh / g at a current density of 0.1C, and the discharge specific capacity is 180 ~ 250mAh / g at a current density of 1C. The capacity retention rate after 300 cycles at a current density of 1C is 75% ~ 95%. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the XRD spectrum of the material prepared in Example 1 of the present invention;

[0023] Figure 2 This is a SEM image of the material prepared in Example 1 of the present invention;

[0024] Figure 3 The discharge specific capacity curves of the materials prepared in Example 1 and Comparative Example 1 of the present invention under 0.1C charge and discharge conditions;

[0025] Figure 4 The discharge specific capacity cycle diagram of the materials prepared in Example 1 and Comparative Example 1 of the present invention under 1C charge and discharge conditions;

[0026] Figure 5 This is a discharge specific capacity cycle diagram of the material prepared in Example 2 of the present invention under 1C charge and discharge conditions;

[0027] Figure 6 This is a discharge specific capacity cycle diagram of the material prepared in Example 3 of the present invention under 1C charge and discharge conditions;

[0028] Figure 7 This is a discharge specific capacity cycle diagram of the material prepared in Comparative Example 2 of the present invention under 1C charge and discharge conditions;

[0029] Figure 8 This is a discharge specific capacity cycle diagram of the material prepared in Comparative Example 3 of the present invention under 1C charge and discharge conditions;

[0030] Fig. 9 This is a discharge specific capacity cycle diagram of the material prepared in comparative example 4 of the present invention under 1C charge and discharge conditions. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing a red phosphorus modified lithium-rich manganese-based positive electrode material, comprising the following steps:

[0032] The lithium-rich manganese-based positive electrode material and red phosphorus are mixed in a mass ratio of 1:0.001-0.01, and calcined at 300-600° C. for 1-6 hours under a vacuum state to obtain a red phosphorus-modified lithium-rich manganese-based positive electrode material;

[0033] The general chemical formula of the lithium-rich manganese-based positive electrode material is: Li 1+x Mn 1-x1 Ni 1-x2 Co 1-x3 O2, x=0.01~0.3, 2+x=x1+x2+x3, x1=0.3~0.6, x2=0.7~1, x3=0.8~1.

[0034] The preparation method provided by the present invention uses low-cost raw materials and has a simple reaction process. After being heated and sublimated at high temperature, red phosphorus undergoes a gas-solid interface reaction with a lithium-rich manganese-based positive electrode material, produces a phosphate coating on the positive electrode surface, and simultaneously forms spinel and oxygen vacancies, thereby achieving P doping inside the positive electrode; the reversibility and structural stability of anion redox of the lithium-rich manganese-based positive electrode material are effectively improved, and the first coulomb efficiency, reversible specific capacity and long-cycle stability of the material are improved.

[0035] In the present invention, the mass ratio of the lithium-rich manganese-based positive electrode material to the phosphorus source is 1:0.001-0.01. The particle size of the red phosphorus is 10-200 μm; and the state of the red phosphorus is gaseous.

[0036] The general chemical formula of the lithium-rich manganese-based positive electrode material in the present invention is: Li 1+x Mn 1-x1 Ni 1-x2 Co 1-x3O2, x = 0.01 ~ 0.3, 2 + x = x1 + x2 + x3, x1 = 0.3 ~ 0.6, x2 = 0.7 ~ 1, x3 = 0.8 ~ 1. The present invention uses a cobalt-containing lithium-rich manganese-based positive electrode material and red phosphorus to improve the material's first coulombic efficiency, reversible specific capacity and long-cycle stability. The lithium-rich manganese-based positive electrode material used in the specific embodiment of the present invention is: Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

[0037] The lithium-rich manganese-based positive electrode material of the present invention is prepared according to the following method:

[0038] Nickel salt, manganese salt, cobalt salt and lithium salt are dissolved in a mixed solution of acrylic acid and deionized water, and an aqueous solution of ammonium persulfate is added. After stirring for 55 to 65 minutes, the temperature is raised to 80°C and kept warm for 170 to 190 minutes for reaction, and then the temperature is raised to 120°C and kept warm for 11 to 13 hours for drying, grinding and two-stage calcination: the first stage calcination temperature is 300 to 600°C and the time is 3 to 7 hours; the second stage calcination temperature is 750 to 950°C and the time is 9 to 15 hours.

[0039] The present invention mixes lithium-rich manganese-based positive electrode materials and red phosphorus uniformly and then adds them into a quartz tube, extracts gas from the quartz tube, and performs high-temperature melting to seal the quartz tube opening, so that the tube is in a vacuum state; the vacuum degree in the vacuum state is 0.01MPa-0.2MPa.

[0040] Then, the quartz tube filled with the material is placed in a muffle furnace for calcination; the calcination temperature is 300-600°C, preferably 430-600°C; the calcination time is 1-6h, preferably 1-5h. The present invention preferably heats to 300-600°C at a heating rate of 2-8°C / min; in a specific embodiment, the heating rate is 2°C / min, 3°C / min and 5°C / min; the calcination temperature is 450°C, 500°C and 600°C; the calcination time is 3h, 2h and 4h.

[0041] The present invention provides a positive electrode sheet, which is prepared by coating a positive electrode slurry on a positive electrode current collector;

[0042] The positive electrode slurry includes a red phosphorus-modified lithium-rich manganese-based positive electrode material prepared by the preparation method described in the above technical solution.

[0043] The positive electrode slurry also includes a conductive agent, a binder and a solvent; the mass ratio of the red phosphorus modified lithium-rich manganese-based positive electrode material, the conductive agent and the binder is 8:1:1. The conductive agent is Super P, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone (NMP).

[0044] The present invention preferably coats the positive electrode slurry on a positive electrode current collector aluminum foil with a thickness of 15 μm. The present invention preferably dries in an oven to obtain a positive electrode sheet; the drying temperature is 110 to 130° C.; and the diameter of the positive electrode sheet is 12 mm.

[0045] The present invention also provides a lithium-ion battery, comprising a negative electrode sheet, an electrolyte, a separator and the positive electrode sheet described in the above technical solution.

[0046] The diaphragm is a PP diaphragm; the negative electrode sheet is a metal lithium sheet; the lithium salt in the electrolyte is LiPF6, and the solvent is a mixed solvent of EC / DEC with a volume ratio of 1:1; the concentration of the lithium salt in the electrolyte is 1 mol / L.

[0047] In order to further illustrate the present invention, the preparation method of a red phosphorus modified lithium-rich manganese-based positive electrode material, the positive electrode sheet and the lithium-ion battery provided by the present invention are described in detail below in combination with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0048] Comparative Example 1

[0049] This comparative example prepares a lithium-rich manganese-based positive electrode material for a lithium-ion battery, and the specific process is as follows:

[0050] 0.3857 g of nickel nitrate hexahydrate, 1.9332 g of 50 wt% manganese nitrate aqueous solution, 0.3727 g of cobalt nitrate hexahydrate and 0.5395 g of lithium hydroxide monohydrate were dissolved in a mixed solution of 2.75 ml of acrylic acid and 1.25 g of deionized water, 300 μL of 5 wt% ammonium persulfate aqueous solution was added, and after stirring for 1 hour, the mixture was moved to a blast oven and heated to 80°C, kept warm for 3 hours for reaction, then heated to 120°C in a blast oven, kept warm for 12 hours for drying, taken out and fully ground, and then calcined in a muffle furnace in two stages: the first stage calcination temperature was 500°C for 6 hours; the second stage calcination temperature was 900°C for 12 hours, and the lithium-rich manganese-based positive electrode material Li was obtained after cooling to room temperature. 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

[0051] Preparation of positive electrode

[0052] The above-mentioned lithium-rich manganese-based positive electrode material, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 8:1:1, and solvent N-methylpyrrolidone (NMP) is added and stirred evenly to obtain a positive electrode slurry, which is then coated on a positive electrode current collector aluminum foil with a thickness of 15 μm, and then dried in a vacuum oven at 120°C and punched into a positive electrode sheet with a diameter of 12 mm.

[0053] Preparation of negative electrode

[0054] The negative electrode directly uses metallic lithium sheets.

[0055] Preparation of electrolyte

[0056] In an argon atmosphere glove box (H2O<0.01ppm, O2<0.01ppm), fully dried lithium salt LiPF6 was dissolved in EC / DEC (volume ratio 1:1) organic solvent to obtain an electrolyte in which the LiPF6 concentration was 1 mol / L.

[0057] Preparation of diaphragm

[0058] Celgard 2400 (PP) was used as the diaphragm and punched into a disc with a diameter of 16 mm.

[0059] Preparation of button cells

[0060] In an argon atmosphere glove box, the positive electrode sheet, the separator, and the metal lithium sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and 60 μL of the above electrolyte is injected to assemble a CR2032 button battery.

[0061] The lithium-rich manganese-based positive electrode material obtained in Comparative Example 1 was assembled into a lithium-ion half-cell, and the electrochemical performance test was performed. Figure 3 As shown in the figure, the first coulombic efficiency of the material is 87.3%. The first discharge specific capacity is 265.5 mAh / g. Figure 4 As shown, the discharge specific capacity at 1C is 204.3 mAh / g, the discharge specific capacity after 300 cycles at 1C is 154.8 mAh / g, and the capacity retention rate is 75.8%.

[0062] Example 1

[0063] The preparation process of the button battery is the same as that of Comparative Example 1, except that:

[0064] Preparation of positive electrode

[0065] The lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 was evenly mixed with red phosphorus in a mass ratio of 1:0.005 and placed in a quartz tube. The gas in the tube was evacuated, and the quartz tube mouth was sealed by high-temperature melting to make the tube in a vacuum state with a vacuum degree of 0.1 MPa. The tube was then placed in a muffle furnace and heated to 500°C at a rate of 2°C / min. After constant temperature calcination for 3 hours, a lithium-rich manganese-based positive electrode material modified with high-temperature red phosphorus was obtained.

[0066] The high-temperature red phosphorus modified lithium-rich manganese-based positive electrode material obtained above is made into a battery according to the following method:

[0067] The high-temperature red phosphorus modified lithium-rich manganese-based positive electrode material, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 8:1:1, and solvent N-methylpyrrolidone (NMP) is added and stirred evenly to obtain a positive electrode slurry, which is then coated on a positive electrode current collector aluminum foil with a thickness of 15 μm, and then dried in a vacuum oven at 120°C and punched into a positive electrode sheet with a diameter of 12 mm.

[0068] The lithium-rich manganese-based cathode material obtained in this example was assembled into a lithium-ion half-cell and the electrochemical performance was tested. Figure 3 As shown in Figure 2, the first coulombic efficiency of the material is as high as 91.5%, and the first discharge capacity exceeds 290 mAh / g. Figure 4 As shown, the discharge capacity at 1C is 239.8 mAh / g, and the discharge capacity after 300 cycles at 1C is 223.9 mAh / g, with a capacity retention rate of 93.4%. Compared with Comparative Example 1, the high-temperature red phosphorus-modified lithium-rich manganese-based positive electrode material has good long-cycle stability and high anion redox reversibility.

[0069] Figure 1 and Figure 2 The XRD and SEM images of the lithium-rich manganese-based lithium-ion battery positive electrode material prepared in this embodiment show single crystal particles of hundreds of nanometers.

[0070] Example 2

[0071] The preparation process of the button cell is the same as that of Example 1, except that:

[0072] Preparation of positive electrode

[0073] The lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 was evenly mixed with red phosphorus in a mass ratio of 1:0.01 and placed in a quartz tube. The gas in the tube was evacuated, and the quartz tube mouth was sealed by high-temperature melting to make the tube in a vacuum state with a vacuum degree of 0.1 MPa. The tube was then placed in a muffle furnace and heated to 600°C at a rate of 5°C / min. After constant temperature calcination for 2 hours, the sample of Example 2 was obtained after cooling.

[0074] like Figure 5 As shown, the discharge specific capacity at 1C is 234.0 mAh / g, the discharge specific capacity after 300 cycles at 1C is 213.8 mAh / g, and the capacity retention rate is 91.4%.

[0075] Example 3

[0076] The preparation process of the button cell is the same as that of Example 1, except that:

[0077] Preparation of positive electrode

[0078] The lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 was uniformly mixed with red phosphorus in a mass ratio of 1:0.001 and placed in a quartz tube. The gas in the tube was evacuated, and the quartz tube mouth was sealed by high-temperature melting to make the tube in a vacuum state with a vacuum degree of 0.1 MPa. The mixture was then placed in a muffle furnace and heated to 450°C at a rate of 3°C / min. After constant temperature calcination for 4 hours, the sample of Example 3 was obtained after cooling.

[0079] like Figure 6 As shown, the discharge specific capacity at 1C is 228.8 mAh / g, the discharge specific capacity after 300 cycles at 1C is 213.7 mAh / g, and the capacity retention rate is 93.4%.

[0080] Comparative Example 2

[0081] This comparative example prepares a lithium-rich manganese-based positive electrode material for a lithium-ion battery, and the specific process is as follows:

[0082] 0.59343 g of nickel nitrate hexahydrate, 2.14800 g of 50 wt% manganese nitrate aqueous solution and 0.53948 g of lithium hydroxide monohydrate were dissolved in a mixed solution of 2.75 ml of acrylic acid and 1.25 g of deionized water, 300 μL of 5 wt% ammonium persulfate aqueous solution was added, and after stirring for 1 hour, the mixture was moved to a blast oven and heated to 80°C, kept warm for 3 hours for reaction, then heated to 120°C in a blast oven, kept warm for 12 hours for drying, taken out and fully ground, and then calcined in a muffle furnace in two stages: the first stage calcination temperature was 500°C for 6 hours; the second stage calcination temperature was 900°C for 12 hours, and after cooling to room temperature, a lithium-rich manganese-based positive electrode material was obtained, whose chemical formula is Li 1.2 Mn 0.6 Ni 0.2 O2.

[0083] The preparation process of the button battery is the same as that of Comparative Example 1.

[0084] like Figure 7 As shown, the discharge specific capacity at 1C is 199.5 mAh / g, the discharge specific capacity after 300 cycles at 1C is 103.85 mAh / g, and the capacity retention rate is 52.1%.

[0085] Comparative Example 3

[0086] The preparation process of the button cell is the same as that of Example 1, except that:

[0087] Preparation of positive electrode

[0088] The lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 was evenly mixed with red phosphorus in a mass ratio of 1:0.01 and placed in a quartz tube. The gas in the tube was evacuated, and the quartz tube mouth was sealed by high-temperature melting to make the tube in a vacuum state. The tube was then placed in a muffle furnace, heated to 700°C at a rate of 5°C / min, calcined at a constant temperature for 2 hours, and then cooled to obtain a sample of Comparative Example 3.

[0089] like Figure 8 As shown, the discharge specific capacity at 1C is 224.7 mAh / g, the discharge specific capacity after 300 cycles at 1C is 161.8 mAh / g, and the capacity retention rate is 72.0%.

[0090] Comparative Example 4

[0091] The preparation process of the button cell is the same as that of Example 1, except that:

[0092] Preparation of positive electrode

[0093] The lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 was evenly mixed with red phosphorus in a mass ratio of 1:0.02 and placed in a quartz tube. The gas in the tube was evacuated, and the quartz tube mouth was sealed by high-temperature melting to make the tube in a vacuum state. The tube was then placed in a muffle furnace, heated to 500°C at a rate of 5°C / min, calcined at a constant temperature for 2 hours, and then cooled to obtain the Comparative Example 4 sample.

[0094] like Fig. 9 As shown, the discharge specific capacity at 1C is 211.2 mAh / g, the discharge specific capacity after 300 cycles at 1C is 154.2 mAh / g, and the capacity retention rate is 73.0%.

[0095] It can be seen from the above embodiments that the present invention provides a method for preparing a lithium-rich manganese-based positive electrode material modified by red phosphorus, comprising the following steps: mixing the lithium-rich manganese-based positive electrode material and red phosphorus in a mass ratio of 1:0.001-0.01, calcining at 300-600°C for 1-6h under vacuum to obtain a lithium-rich manganese-based positive electrode material modified by red phosphorus; the chemical formula of the lithium-rich manganese-based positive electrode material is: Li 1+x Mn 1-x1 Ni 1-x2 Co 1-x3O2, x = 0.01 ~ 0.3, 2 + x = x1 + x2 + x3, x1 = 0.3 ~ 0.6, x2 = 0.7 ~ 1, x3 = 0.8 ~ 1. This method has low raw material price and simple reaction process. After high temperature heating and sublimation, red phosphorus reacts with lithium-rich manganese-based positive electrode materials to produce a phosphate coating on the surface of the positive electrode, while forming spinel and oxygen vacancies, and realizing P doping inside the positive electrode. It effectively improves the reversibility and structural stability of anion redox of lithium-rich manganese-based positive electrode materials, and improves the first coulomb efficiency, reversible specific capacity and long cycle stability of the material. The experimental results show that the discharge specific capacity of the lithium-rich manganese-based positive electrode material of the present invention is 250 ~ 300mAh / g at a current density of 0.1C, and the discharge specific capacity is 180 ~ 250mAh / g at a current density of 1C. The capacity retention rate after 300 cycles at a current density of 1C is 75% to 95%.

[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a red phosphorus-modified lithium-rich manganese-based positive electrode material, comprising the following steps: The lithium-rich manganese-based positive electrode material and red phosphorus are mixed in a mass ratio of 1:0.001-0.01, and calcined at 300-600° C. for 1-6 hours under a vacuum state to obtain a red phosphorus-modified lithium-rich manganese-based positive electrode material; The general chemical formula of the lithium-rich manganese-based positive electrode material is: Li 1+x Mn 1-x1 Ni 1-x2 Co 1-x3 O2, x=0.01~0.3, 2+x=x1+x2+x3, x1=0.3~0.6, x2=0.7~1, x3=0.8~1.

2. The preparation method according to claim 1, characterized in that: The particle size of the red phosphorus is 10 to 200 μm; Red phosphorus is in gaseous state.

3. The preparation method according to claim 1, characterized in that: The vacuum degree under the vacuum state is 0.01MPa to 0.2MPa.

4. The preparation method according to claim 1, characterized in that: The temperature is increased to 300-600°C at a heating rate of 2-8°C / min.

5. The preparation method according to claim 1, characterized in that: The lithium-rich manganese-based positive electrode material is: Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

6. The preparation method according to claim 1, characterized in that: The lithium-rich manganese-based positive electrode material is prepared according to the following method: Nickel salt, manganese salt, cobalt salt and lithium salt are dissolved in a mixed solution of acrylic acid and deionized water, and an aqueous solution of ammonium persulfate is added. After stirring for 55 to 65 minutes, the temperature is raised to 80°C and kept warm for 170 to 190 minutes for reaction, and then the temperature is raised to 120°C and kept warm for 11 to 13 hours for drying, grinding and two-stage calcination: the first stage calcination temperature is 300 to 600°C and the time is 3 to 7 hours; the second stage calcination temperature is 750 to 950°C and the time is 9 to 15 hours.

7. A positive electrode sheet, prepared by coating a positive electrode slurry on a positive electrode current collector; The positive electrode slurry comprises a red phosphorus-modified lithium-rich manganese-based positive electrode material prepared by the preparation method of any one of claims 1 to 6.

8. A lithium ion battery, characterized in that: The invention comprises a negative electrode sheet, an electrolyte, a separator and the positive electrode sheet as claimed in claim 8.

9. The lithium-ion battery according to claim 8, characterized in that: The separator is a PP separator; the negative electrode sheet is a metal lithium sheet; The lithium salt in the electrolyte is LiPF6, and the solvent is a mixed solvent of EC / DEC with a volume ratio of 1:1.

Citation Information

Patent Citations

  • Composite cation-doped manganese-based solid-solution positive electrode material and preparation method thereof

    CN103515593A

  • Phosphorus-modified lithium ion battery positive electrode material and preparation method and application thereof

    CN112054194A

  • Low-temperature vapor deposition coated high-nickel ternary layered positive electrode material and preparation method thereof

    CN112768662A

  • Method for improving specific discharge capacity and cycling stability of lithium-rich positive electrode material through gas phase surface phosphating treatment and material

    CN113161535A

  • Surface-modified lithium-rich manganese-based positive electrode material and preparation method thereof

    CN115548290A

Cited By

  • Lithium-rich manganese-based positive electrode material containing coating layer and application of lithium-rich manganese-based positive electrode material in all-solid-state lithium battery

    CN119864405A